PENGARUH PROFITABILITAS, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DENGAN KUALITAS AUDIT SEBAGAI VARIABEL MODERASI - Himawan, F Agung; Kurniawan, Niko; Wibowo, Edi Wahyu (JURNAL LENTERA BISNIS, 2026)
This study aims to examine the effect of profitability, leverage, and company size on corporate social responsibility, with audit quality as a moderating variable, in energy sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019–2023 period. This study uses a quantitative approach with secondary data obtained from annual financial reports and corporate sustainability reports. The study sample consisted of 18 energy sector companies listed on the IDX, with a total sample size of 95 company financial reports. The data analysis technique used was multiple linear regression analysis. The results of this study indicate that (1) profitability has a significant positive effect on CSR disclosure, (2) leverage has no effect on CSR disclosure, (3) company size has a significant positive effect on CSR disclosure, and (4) audit quality weakens the relationship between profitability, leverage, and company size on CSR disclosure.